Coulomb-mediated antibunching of an electron pair surfing on sound - Wang, Junliang; Edlbauer, Hermann; Richard, Aymeric; Ota, Shunsuke; Park, Wanki; Shim, Jeongmin; Ludwig, Arne; Wieck, Andreas D.; Sim, Heung-Sun; Urdampilleta, Matias; Meunier, Tristan; Kodera, Tetsuo; et al. (Nature nanotechnology, 2023)
Electron flying qubits are envisioned as potential information links within a quantum computer, but also promise—like photonic approaches—to serve as self-standing quantum processing units. In contrast to their photonic counterparts, electron-quantum-optics implementations are subject to Coulomb interactions, which provide a direct route to entangle the orbital or spin degree of freedom. However, controlled interaction of flying electrons at the single-particle level has not yet been established experimentally. Here we report antibunching of a pair of single electrons that is synchronously shuttled through a circuit of coupled quantum rails by means of a surface acoustic wave. The in-flight partitioning process exhibits a reciprocal gating effect which allows us to ascribe the observed repulsion predominantly to Coulomb interaction. Our single-shot experiment marks an important milestone on the route to realize a controlled-phase gate for in-flight quantum manipulations. Collisions between two individual electrons in a quantum nanoelectronic circuit revealed a mutual interaction fully mediated by Coulomb repulsion—an essential building block for two-qubit logic implementations with flying electrons.